Developing a Coaching Model to Promote Teachers’ Potential for Conducting Classroom Research - Ladda Wangphasit,; Kridsana Mookkaew, (Journal of Educational Issues, 2024)
This study aimed to 1) develop a coaching model to promote teachers’ potential to conduct classroom research and 2) evaluate the effectiveness of the coaching model. The research methodology consisted of three phases. In the first phase, the researcher studied the related studies and interviewed various experts about conducting classroom research and coaching. In the second phase, the researcher developed a coaching model and research instruments and asked experts to validate these, and these were then trialed in a pilot study. In the third phase, the researcher investigated the effectiveness of the coaching model for promoting teachers’ potential to conduct classroom research via a one-group pre-test and post-test design. The intervention group in the present study comprised 147 teachers teaching at Islamic Schools in Bangkok, which are private schools operating under the Office of the Private Education Commission, in the 2020 academic year. The experiment lasted for 20 weeks. Two classes were run each week, for 20 weeks, for a total of 40 classes over the study period, and workshops were run before and after the intervention. The data obtained were analyzed by dependent t-test. It was found that the optimum coaching model for promoting teachers’ potential for conducting classroom research comprised three steps: 1) empowerment, 2) co-creation, and 3) enlargement. Further, the teachers’ potential for conducting classroom research was higher after the experiment than before the experiment with statistical significance at 0.50. Most of the research quality was at a good level (X̄ = 77.87; S.D. 1.60).